Three methods to determine mass characteristics of human body segments - Schüler, A.; Schleichardt, A.; Hildebrand, F.; Witt, M. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
Three approaches to estimate body segment parameters (BSP) are compared, a volumescanning photographic method, a force plate technique and a geometric method. First approach: a 3D body scanner was used to obtain a closed surface mesh of a subject. Closed loops were employed to divide the mesh into head, thorax, pelvis and limbs. Volume and center of mass (CM) of each segment were computed. Second approach: a triangular reaction board with two force sensors was used to measure the position of the CM. Third approach: The multi-body simulation software dynamicus/alaska models the segments by geometric shapes like elliptic solids, ellipsoids, and semi-ellipsoids. The results indicate that the body scanner method is highly accurate and an integration into dynamicus/alaska would increase simulation accuracy.